Comparing the Safety and Efficacy of Phacogoniosynechialysis With Phacotrabeculectomy in the Management of Refractory Acute Primary Closure Angle Glaucoma With Cataract: A Multicenter Randomized Trial. Issue 7 (11th July 2021) - Nguyen Xuan, Hiep; Nguyen Dinh, Ngan; Nguyen Thu, Huong; Nguyen Van, Cuong; Aung, Tin; Loo, Yunhua; Nguyen Do Thi Ngoc, Hien; Do, Tan
Abstract : Précis: Combined phacoemulsification-goniosynechialysis (phaco-GSL) and unaugmented phacotrabeculectomy were both found to be effective in treating eyes with significant cataract and medically unresponsive acute primary angle closure glaucoma (PACG). Phaco-GSL seemed to be safer, with fewer surgical complications, and achieved better visual acuity than phacotrabeculectomy. Objectives: To compare the results of combined phaco-GSL with unaugmented phacotrabeculectomy in the management of eyes with medically unresponsive acute PACG and cataract. Participants and Research Methods: This was a prospective randomized controlled trial involving patients with significant cataract and acute PACG who were not responsive to maximal medical therapy. Three ophthalmic centers in Hanoi, Vietnam, participated in this trial. Study subjects were randomized into 2 groups: phaco-GSL or phacotrabeculectomy. Of note, mitomycin-C or 5-fluorouracil were not used during trabeculectomy, but postoperative bleb needling with 5-fluorouracil injection(s) was allowed. The primary outcome of the study was the rate of postoperative surgical complications in the first 3 months after surgery. The secondary outcome, determined at 1 year, assessed whether treatment was completely successful [defined as intraocular pressure (IOP)<21 mm Hg without IOP-lowering drops], or partially successful (IOP<21 mm Hg with IOP-lowering drops). Treatment failure was defined as IOP≥21 mm Hg with maximal IOP-lowering drops. Results: In total, 79 eyes from 79 patients (62 females, 17 males) were recruited (42 and 37 eyes in the phaco-GSL and phacotrabeculectomy groups, respectively). There were no statistically significant differences between the 2 groups at baseline in terms of age, visual acuity, IOP, anterior angle width, or preoperative ultrasound biomicroscopy index. Postoperative complications in the first 3 months were seen more frequently in the phacotrabeculectomy group (62.2%) than in the phaco-GSL group (14.3%, P <0.01). At 1 year postsurgery, treatment was 100% successful in both groups, with no difference in the mean IOP (15.38±3.42 vs. 15.72±4.47 mm Hg). The visual field index improved significantly following surgery in both groups, but there was also no significant difference between the 2 groups. However, there was a significant difference in the best corrected visual acuity at 1 year, with patients in the phaco-GSL group achieving better vision (0.45±0.21 logMAR in the phaco-GSL group vs. 0.64±0.27 logMAR in the phacotrabeculectomy group, P =0.04). The mean angle width was also significantly larger in the phaco-GSL group than the phacotrabeculectomy group (2.34±0.33 vs. 1.25±0.41 Shaffer degrees). Similarly, on ultrasound biomicroscopy, the anterior chamber was deeper after 12 months (2.87±0.28 to 2.48±0.33 mm), and the mean trabecular-iris angle area was wider at 12 months (21.88±7.07 vs. 14.95±4.39 degrees) in the phaco-GSL than the phacotrabeculectomy group. Conclusions: Phaco-GSL and phacotrabeculectomy were both effective in treating medically unresponsive cases of acute PACG with cataracts. However, phaco-GSL showed better visual outcomes, wider drainage angles postsurgery, and fewer complications than phacotrabeculectomy.